THE CINEMATIC CANVAS: A COMPREHENSIVE EXPLORATION OF CINEMA AS A THERAPY, EFFECT OF FILM ON EMOTIONAL INSIGHT, HEALING, AND PERSONAL WELLBEING - V., Prabakaran; Padmavathy, P. S. (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Cinematherapy, also known as film therapy or movie therapy, was formally coined by Berg-Cross, Jennings and Baruch (1990) is a therapeutic approach that utilizes the power of cinema to promote emotional healing and personal growth. This innovative approach draws upon various psychological theories, including psychoanalysis, cognitive-behavioral theory, and humanistic theory, to help individuals explore their emotions, gain new perspectives, and develop coping skills. This study provides a comprehensive review of the theoretical foundations, historical roots, and practical applications of cinema as a therapeutic tool. Through a critical analysis of existing literature and empirical studies, this study aims to contribute to the growing body of research on cinematherapy and its effectiveness in promoting mental health and well-being. The findings suggest that cinematherapy can be a valuable adjunct to traditional psychotherapy, offering clients a unique and engaging way to explore their thoughts, feelings, and experiences. Further research is needed to fully understand the potential of cinematherapy and its role in enhancing therapeutic outcomes.